THE EFFECT OF DRILL TRAINING METHODS ON BASIC PASSING SKILLS IN FUTSAL AMONG EXTRACURRICULAR STUDENTS AT YAPERMAS JUNIOR HIGH SCHOOL - Adhim, Muhammad Fauzhil; Sitompul, Surya Rezeki; Aspar, Muhammad (Program Studi Pendidikan Jasmani, FKIP Universitas Bina Bangsa Getsempena, 2025)
Passing is a fundamental technique in futsal that every player must master, as it is crucial for maintaining possession, controlling the tempo, and creating scoring opportunities. Yet, observations in the futsal extracurricular program at SMP YAPERMAS showed that many students experienced difficulties with accuracy and power, which disrupted effective ball control among teammates. Results from a basic passing technique test further revealed that students’ average performance was categorized as “very poor,” emphasizing the importance of structured training to enhance this skill. This study aimed to analyze the effect of drill training on the passing abilities of extracurricular futsal participants at SMP YAPERMAS. This study employed a quantitative method with a pre-experimental design involving one group that received both pretest and posttest measurements. The research population comprised 18 students, with 12 purposively selected as samples. Participants were required to be male, physically and mentally fit, actively involved in extracurricular futsal, willing to participate, and registered as seventh or eighth graders in the 2024–2025 academic year. The findings indicated significant improvement in passing performance, as shown by an increase in the mean score from 57.67 in the pretest to 64.59 in the posttest. Statistical analysis using a paired sample t-test with SPSS 25 yielded a significance level of 0.00, which is below the 0.05 threshold. These results confirm that the drill training method positively and significantly influenced students’ basic passing techniques, proving its effectiveness as a training strategy in school-based futsal programs.